Gerencia de la competitividad e innovación para el mejoramiento continuo en las Pymes de Florencia-Caquetá. (2020)
The result presented comprises the product of the research developed in the year 2017, with Pymes in the Municipality of Florencia, Caquetá, in where they show up and show results on the ability of the innovation as an essential element for the development of competitiveness, an important aspect in the improvement of the productive growth and economic of these companies. The study was conducted with 374 firms, randomly selected from a total population of approximately 8,000 are registered at the Chamber of Commerce. The approach applied was to cut quantitative, with a design methodology descriptive. The instrument used was a survey applied to managers of companies under study, whose analysis was based on the tabulation of statistical data in IBM SPSS software.